The Natural History and Treatment Options for Unruptured Intracranial Aneurysms - Joshua E. Loewenstein; Shaneze C. Gayle; E. Jesus Duffis; Charles J. Prestigiacomo; Chirag D. Gandhi (International Journal of Vascular Medicine)
Recent advances in angiographic technique have raised our awareness of the presence of unruptured intracranial aneurysms (UIAs). However, the appropriate management for these lesions remains controversial. To optimize patient outcomes, the physician must weigh aneurysmal rupture risk associated with observation against the complication risks associated with intervention. In the case that treatment is chosen, the two available options are surgical clipping and endovascular coiling. Our paper summarizes the current body of literature in regards to the natural history of UIAs, the evolution of the lesion if it progresses uninterrupted, as well as the safety and efficacy of both treatment options. The risks and benefits of treatment and conservative management need to be evaluated on an individual basis and are greatly effected by both patient-specific and aneurysm-specific factors, which are presented in this paper. Ultimately, this body of data has led to multiple sets of treatment guidelines, which we have summated and presented in this paper.